Missing OH source in a suburban environment near Beijing: observed and modelled OH and HO2 concentrations in summer 2006 - Lu, Keding; Hofzumahaus, Andreas; Holland, Frank; Bohn, Birger; Brauers, Theo; Fuchs, Hendrik; Min Hu; Rolf Häseler; Kita, Kazuyuki; Kondo, Yutaka; Xin Li; Shengrong Lou; et al. (Atmospheric Chemistry and Physics, 2013)
Measurements of ambient OH and HO2 radicals were performed by laser induced fluorescence (LIF) during CAREBeijing2006 (Campaigns of Air Quality Research in Beijing and Surrounding Region 2006) at the suburban site Yufa in the south of Beijing in summer 2006. On most days, local air chemistry was influenced by aged air pollution that was advected by a slow, almost stagnant wind from southern regions. Observed daily concentration maxima were in the range of (4-17) x 10(6) cm(-3) for OH and (2-24) x 10(8) cm(-3) for HO2 (including an estimated interference of 25% from RO2). During daytime, OH reactivities were generally high (10-30 s(-1)) and mainly contributed by observed VOCs and their calculated oxidation products. The comparison of modelled and measured HOx concentrations reveals a systematic underprediction of OH as a function of NO. A large discrepancy of a factor 2.6 is found at the lowest NO concentration encountered (0.1 ppb), whereas the discrepancy becomes insignificant above 1 ppb NO. This study extends similar observations from the Pearl-River Delta (PRD) in South China to a more urban environment. The OH discrepancy at Yufa can be resolved, if NO-independent additional OH recycling is assumed in the model. The postulated Leuven Isoprene Mechanism (LIM) has the potential to explain the gap between modelled and measured OH at Beijing taking into account conservative error estimates, but lacks experimental confirmation. This and the hereby unresolved discrepancy at PRD suggest that other VOCs besides isoprene might be involved in the required, additional OH recycling. Fast primary production of ROx radicals up to 7 ppb h(-1) was determined at Beijing which was dominated by the photolysis of O-3, HONO, HCHO, and dicarbonyls. For a special case, 20 August, when the plume of Beijing city was encountered, a missing primary HOx source (about 3 ppb h(-1)) was determined under high NOx conditions similar to other urban areas like Mexico City. CAREBeijing2006 emphasizes the important role of OVOCs as a radical source and sink, and the need for further investigation of the chemical degradation of VOCs in order to better understand radical chemistry in VOC-rich air.